Penyelesaian Isykāl Hadis Mayat Diazab karena Ratapan - Arfan; Afni A., Nur (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This research discusses the isykāl hadith about corps being punished by wailing along with the scholars' resolution of this isykāl. This research uses a descriptive method through a content analysis approach, through literature review, both books written by classical scholars and scientific books and articles compiled by contemporary researchers, as well as other relevant sources. The hadiths which are the object of study are only taken from al-Ṣaḥīḥain or one of the two so that the author no longer criticizes the sanad but instead goes directly to the analysis of the existing matan-matan. Next, all the information obtained during the research will be analyzed to draw the conclusions. The results of this research found that isykāl in the hadith of corpses being tortured because of wailing is a hadith which is considered to be contrary to the verse of the Al-Qur’an, namely